Diagnosis and molecular epidemiology of bovine rotavirus and coronarvirus in Brazil - Jakobsson, Samuel (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2013)
Rotavirus and coronavirus are the two most common viral causes of neonatal calf diarrhea and their presence causes a lot of economic damage to the farmers as well as suffering to the animal. By getting better knowledge about the viruses we may help in tracing transmission and in producing new vaccines. This paper served to study the molecular epidemiology of rotavirus and coronavirus in fecal samples collected from two different farms in the state of São Paulo, Brazil. These samples have been studied with focus on the gene VP4, VP7, NSP4 in rotavirus and the gene S1 in coronavirus. From the first farm the screening PCR showed that 12/48 samples were positive for rotavirus and 4/48 positive for coronavirus. No determination of genotypes of rotavirus was achieved and the sequences retrieved did not match any known rotavirus. Nor was any amplification and sequencing of the positive samples of coronavirus successful. From the second farm 14/22 samples tested positive for rotavirus and 2/22 samples positive for coronavirus. Initial genotyping PCR for determination of G- and P-genotype identified 3 samples as G6, 5 samples as P[1] and 1 sample as P[11]. Successful sequencing confirmed that the 3 samples were of genotype G6 but identified the, by genotyping PCR determined, P[1] samples as P[5]. From the coronavirus positive samples one sequence which clustered within the genus betacoronaviruses were retrieved.